2020
DOI: 10.1002/jcsm.12532
|View full text |Cite
|
Sign up to set email alerts
|

Improving rehabilitation in sarcopenia: a randomized‐controlled trial utilizing a muscle‐targeted food for special medical purposes

Abstract: Background Sarcopenia is a disease associated with aging and a negative prognosis. Consensus-based treatment consists in targeting muscle mass and function through physical exercise, optimization of protein intake, and vitamin D supplementation, but evidence is lacking. We evaluated the safety and efficacy of a muscle-targeted nutritional support on the outcome of a physical exercise rehabilitation programme. Methods In a single-site, double-blind, randomized, controlled trial (NCT03120026; May 2017 to Decembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(117 citation statements)
references
References 54 publications
2
74
0
Order By: Relevance
“…Various studies indicate that older adults require a daily protein intake of 1.0 to 1.2g / kg body weight to support muscle health and function. 38,81 In well-controlled and powered RCTs of sarcopenic older adults, supplementation using whey protein enhances muscle mass and function 82 83 and prevents mobility impairment. 84 85 Our team recently showed in a 2-year clustered-randomised nutrition intervention involving over 7,000 older adults in aged-care that increased dietary protein (from 0.9 to 1.1g/kg body weight) and calcium intakes were associated with maintenance of appendicular muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies indicate that older adults require a daily protein intake of 1.0 to 1.2g / kg body weight to support muscle health and function. 38,81 In well-controlled and powered RCTs of sarcopenic older adults, supplementation using whey protein enhances muscle mass and function 82 83 and prevents mobility impairment. 84 85 Our team recently showed in a 2-year clustered-randomised nutrition intervention involving over 7,000 older adults in aged-care that increased dietary protein (from 0.9 to 1.1g/kg body weight) and calcium intakes were associated with maintenance of appendicular muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of whey protein, leucine and vitamin D in the study product has been shown to stimulate muscle protein synthesis 35–37 and increase muscle mass, as well as lower extremity function in sarcopenic older adults. 31 38 …”
Section: Methods and Analysismentioning
confidence: 99%
“…By combining an individualised physical rehabilitation programme with a muscle-targeted ONS (20-g whey protein, 2.8-g leucine, 800-IU vitamin D and 500-mg calcium) twice daily for 4–8 weeks, compared to a control group who received an iso-caloric protein-free drink, cost-effective improvements were seen for their physical performance, physical function and muscle mass. In those who received the muscle-targeted supplement, a greater proportion were discharged home instead of to a care facility (+24%), had a reduction in intensity of care at discharge (+22%), needed less rehabilitation (−27% in duration) and had a shorter length of stay (−10 days) [ 61 ].…”
Section: Ensure Continuity Of Nutritional Therapy After Dischargementioning
confidence: 99%